Lightweight ambient-cured geopolymer composite with expanded clay: quasi-static and dynamic properties - Li, Zhixing; Chen, Wensu; Yin, Z.; Ahmed, Mizan; Hao, Hong (2024)
The increased awareness of sustainability and concerns about global warming have prompted the construction industry to explore green sustainable materials such as geopolymer composites as an eco-friendly alternative to ordinary Portland cement (OPC). This study developed ambient-cured lightweight geopolymer composites (LWGPCs) by incorporating different volume fractions of expanded clay (EC). The physical and quasi-static characteristics of LWGPCs with various EC contents were investigated. Empirical formulae for the quasi-static compressive and splitting tensile strength, as well as the elastic modulus of LWGPCs were proposed. A Ø 100-mm split Hopkinson pressure bar (SHPB) system was employed to investigate the dynamic compressive and splitting tensile properties of LWGPCs. The failure processes and failure patterns of LWGPCs, as well as the stress–strain curves and the energy absorption capacities under different strain rates were compared. Based on the testing results, empirical formulae of the DIF (dynamic increase factor) for LWGPCs compressive and split tensile strength as well as the energy absorption capacities were proposed. This study offers valuable insights into the material performance of ambient-cured LWGPCs with EC as sustainable materials under quasi-static and dynamic loading, paving the way for further developing and application of lightweight and sustainable engineering materials in construction.